2010
DOI: 10.1186/1476-072x-9-33
|View full text |Cite
|
Sign up to set email alerts
|

A modified version of Moran's I

Abstract: BackgroundInvestigation of global clustering patterns across regions is very important in spatial data analysis. Moran's I is a widely used spatial statistic for detecting global spatial patterns such as an east-west trend or an unusually large cluster. Here, we intend to improve Moran's I for evaluating global clustering patterns by including the weight function in the variance, introducing a population density (PD) weight function in the statistics, and conducting Monte Carlo simulation for testing. We compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 25 publications
4
45
0
Order By: Relevance
“…To evaluate the degree of similarity of observation across space, global indices of spatial autocorrelation are commonly used (Jackson et al, 2010). Moran's I is a global index of spatial autocorrelation widely used and tested for studying spatial autocorrelation over the past 50 years (Bae et al, 2008;Jackson et al, 2010;Young and Jensen, 2012;Zhang and Lin, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the degree of similarity of observation across space, global indices of spatial autocorrelation are commonly used (Jackson et al, 2010). Moran's I is a global index of spatial autocorrelation widely used and tested for studying spatial autocorrelation over the past 50 years (Bae et al, 2008;Jackson et al, 2010;Young and Jensen, 2012;Zhang and Lin, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the degree of similarity of observation across space, global indices of spatial autocorrelation are commonly used (Jackson et al, 2010). Moran's I is a global index of spatial autocorrelation widely used and tested for studying spatial autocorrelation over the past 50 years (Bae et al, 2008;Jackson et al, 2010;Young and Jensen, 2012;Zhang and Lin, 2007). On the other hand, while global indices like Moran's I can measure spatial association of the entire data set, use of local indicators for association local spatial clusters (LISA, Anselin, 1995) is needed to identify clusters of high (hot) and low (col) spots across space (Bae et al, 2008;Rossen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A modified version of Moran’s I (18) was used to test for geographic clustering for the three dependent variables. Modified Moran’s I is defined as: IWMathClass-rel=MathClass-op∑iMathClass-rel=1NMathClass-op∑{jMathClass-punc:jMathClass-rel≠i}NWitalicij(ÎłiMathClass-bin−falsemml-overlineγ¯)(ÎłjMathClass-bin−falsemml-overlineγ¯)MathClass-op∑1MathClass-rel≀iMathClass-rel<jMathClass-rel≀NWitalicij(ÎłiMathClass-bin−γj)2MathClass-punc, where Îł i and Îł j are the colorectal death rates at geographic locations i and j , respectively; falsemml-overlineγ¯ is the expected colorectal death rate using all the data; and N is the total number of geographic units.…”
Section: Methodsmentioning
confidence: 99%
“…They have reported that for both α and ÎČ tree diversities, the distance of the spatial autocorrelation increased slightly at the scale of 10-15 and 200 km and decreased around 20-40 km. Modified version of Moran's I: Traditional calculation of Moran's I for heterogeneous populations is not working well (Jackson et al, 2010). Therefore, several alternative version of Moran's I have been proposed to account for heterogeneous population, for example Oden (1995);Waldhor (1996); Assuncao and Reis (1999) and Waller et al (2006).…”
Section: Global Autocorrelationmentioning
confidence: 99%
“…In order to capture the variability present in the region, Oden includes the first term in the numerator which is used to model the spatial variation in a manner similar to conventional chisquared for heterogeneity rates. The odens's I* pop can be written as Jackson et al (2010) improves the original version of Moran's I by incorporation of (a) a weight function in the variance computation (b) introducing the population density weight function and (c) conducting Monte Carlo simulation. Their weight function is not only included in the differences of the geographic unit's cases from the overall mean, but also in the calculation of the variance.…”
Section: Global Autocorrelationmentioning
confidence: 99%